Problemy ewidencji księgowej instrumentów pochodnych w kontekście postępującej harmonizacji rachunkowości w Unii Europejskiej - Dziawgo, Danuta (Problems with Derivatives' Accounting Records in the Context of Progressing Harmonisation of Accountancy in the European Union, 2006)
As a result of the increasing requirements concerning fast, complete and adequate information on the subject of economy processes the role of the accountancy is growing. This role grew over i along with the progressing process of goods exchange and technical development. Among the challenges of the accountancy, the issues of reserves and derivatives should be mentioned liar. г paper, the crucial problems connected with proper accounting of derivatives with respect of accountancy roles are presented. A special attention is drawn to difficulties connected with a proper i of the influence of transactions with the use of derivatives on financial result. Also, the the possibilities of creating of financial result through the transactions are stressed. The necessity of treatment of derivatives within balance sheet accounting or tax accounting is also pointed out. Theoretical considerations are enriched with selected cases.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 191-203